A Preliminary Study on Technological Innovation Capabilities (TICs) and Competitive Advantage in the Automotive Industry in Malaysia - Faridah, Taju Rahim; Yuserrie, Zainuddin (Universiti Tenaga Nasional., 2017)
This study investigates the relationship of TIC dimensions on competitive advantage in the automotive industry in Malaysia.The purpose of this paper is to present the research model along side hypotheses development, and the results of a preliminary study on these relationships. A pilot study was conducted, with the aim of assessing the validity and reliability of the instruments that are designed to be replicated in the main survey. The PLS-SEM measurement model was applied to measure the reliability and validity of the items in this study. The results indicate that the measuring instruments are reliable and the data for pilot study showed a strong evidence of construct validity in terms of convergent and discriminate validity and there is no collinearity problem between the first-order constructs.